A Spondylo Epi (meta) Physeal Dysplasia: Hypocalcitonemia in Handigodu Disease - Badadani, Mallikarjun; Shetty, K. Taranath; Agarwal, S. S. (Highlights on Medicine and Medical Research Vol. 13, 2021)
Handigodu Disease (HD) is a disorder of the osteoarticular system which is highly prevalent in several villages of two districts viz, Shimoga and Chikmaglur of the state of Karnataka, southern India. It is a rare and painful osteoarthritic disorder. The disease is known scientifically as Spondylo-epi-(meta)physeal Dysplasia, Autosomal Dominant variety, Handigodu syndrome. The International Classification of Skeletal Dysplasias has the same classification. In HD, there was no calcium homeostasis study. After an overnight fast, serum calcium, phosphorus, parathyroid hormone, and calcitonin levels were measured, as well as calcium and phosphorus urinary excretion for 24 hours. In HD, there was a decrease in calcitonin levels, which was associated with a decrease in serum total calcium and urinary calcium. The levels of parathyroid hormone, serum phosphorus, and urinary phosphorus in HD patients remain unchanged. Vitamin D3 levels were also found to be unchanged in HD patients. Because calcitonin has an antiresorption effect on bone, the observed low calcitonin in HD may indicate resorption of bone, which causes deformity and hypocalcaemia and hypocalciuria. The hypocalcitonemia without change in iPTH associated with hypocalcaemia could be due to a mutation in the Vit D receptor (VDR) or it could be an epiphenomenon.